2004
DOI: 10.1097/01.aog.0000147597.45349.e8
|View full text |Cite
|
Sign up to set email alerts
|

Anal Incontinence After Vaginal Delivery: A Five-Year Prospective Cohort Study

Abstract: Anal incontinence among primiparous women increases over time and is affected by further childbirth. Anal incontinence at 9 months postpartum is an important predictor of persisting symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
109
3
8

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(126 citation statements)
references
References 16 publications
6
109
3
8
Order By: Relevance
“…Birth in water is not associated with an increased risk for AST and results in less episiotomies. Given the high rate of anal incontinence 5 years after an AST [14] , women should be informed before birth about the association of certain birth positions with the occurrence of AST. Due to the retrospective design of the study, our results have to be confirmed in a prospectively designed study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Birth in water is not associated with an increased risk for AST and results in less episiotomies. Given the high rate of anal incontinence 5 years after an AST [14] , women should be informed before birth about the association of certain birth positions with the occurrence of AST. Due to the retrospective design of the study, our results have to be confirmed in a prospectively designed study.…”
Section: Resultsmentioning
confidence: 99%
“…There is an established association between sphincter muscle damage and anal incontinence reaching up to 53% 5 years after delivery [14] . Furthermore, these defects have significant effects on emotional health, such as anxiety and depression [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Pollack et al 3 demonstrated that women with subsequent childbirths had significantly elevated odds of anal incontinence, suggesting that, among women with one vaginal delivery, 58.3% of anal incontinence could be attributed to subsequent childbirths. Mant et al 4 found that, compared with nulliparous women, women with one child had four times higher odds and women with two children had 8.4 times higher odds of the development of pelvic organ prolapse (POP) requiring hospital admission.…”
Section: Authors' Replymentioning
confidence: 99%
“…3 Such complications are unsurprising given the extent and nature of the tissue injury, which includes wideranging denervation. It is also clear that extensive peripheral nerve injury results in changes in the central nervous system, such that surgery results in high rates of recurrent pain in the short to medium term.…”
Section: Sirmentioning
confidence: 99%